2020
DOI: 10.4103/wjnm.wjnm_17_20
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and metabolic evolution of prostate cancer lung metastasis detected by prostate-specific membrane antigen and fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography

Abstract: We describe the case of a 75-year-old patient who progressed over a 12-year period from localized to symptomatic metastatic prostate cancer (PrCa) with lung as the sole organ of involvement. In this case, the specific sequence of positron emission tomography (PET)-based next-generation imaging with 18 F-sodium fluoride-, 18 F-fluoro-2-deoxy-D-glucose-, and 18 F-DCFPyL PET/computed tomography and biopsies allowed illustration of the pathway of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Specifically, patients with lung metastasis tend to experience a more favorable disease course compared to other sites of visceral metastasis [8]. As in Table 1, prognosis and survival outcomes in prostate cancer lung metastasis vary significantly according to the present studies, with survival ranging from 3 to 88 months and a median survival of 26 months [13,15,17,18,20,21,[23][24][25]28,29,37,39,40,49,51,52,[62][63][64][65][66][67]69,70,[73][74][75]85,86,[91][92][93][94][95][96]. The survival outcomes depend on several factors, including the extent of metastatic spread, the aggressiveness of the disease, the presence of comorbidities, and the effectiveness of treatment interventions [76].…”
Section: Prognosis and Oncological Outcomesmentioning
confidence: 62%
See 3 more Smart Citations
“…Specifically, patients with lung metastasis tend to experience a more favorable disease course compared to other sites of visceral metastasis [8]. As in Table 1, prognosis and survival outcomes in prostate cancer lung metastasis vary significantly according to the present studies, with survival ranging from 3 to 88 months and a median survival of 26 months [13,15,17,18,20,21,[23][24][25]28,29,37,39,40,49,51,52,[62][63][64][65][66][67]69,70,[73][74][75]85,86,[91][92][93][94][95][96]. The survival outcomes depend on several factors, including the extent of metastatic spread, the aggressiveness of the disease, the presence of comorbidities, and the effectiveness of treatment interventions [76].…”
Section: Prognosis and Oncological Outcomesmentioning
confidence: 62%
“…By curtailing the production of testosterone and other androgens, ADT exerts palliative effects, effectively slowing the advancement of metastatic prostate cancer. This therapeutic strategy remains a cornerstone in the treatment arsenal, contributing significantly to improving patient outcomes [12,15,17,18,20,21,23,25,28,29,39,40,52,[62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Another class which is the ARPIs represent promising therapeutic options in the management of prostate cancer lung metastasis, offering targeted inhibition of the androgen receptor pathway to impede disease progression and alleviate symptoms [29,74].…”
Section: Systemic Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As in Table 1 , most of the patients across all the studies were asymptomatic, while only 13 out of the 58 studies included reported variable clinical symptoms ranging from general symptoms such as hematuria, increased urinary frequency, and weight loss to pulmonary symptoms like cough, dyspnea, chest pain, and hemoptysis [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Several factors contributed to the presenting symptoms, including the number and location of the metastatic lesions.…”
Section: Prostate Cancer Lung Metastasis Presentationsmentioning
confidence: 99%